Greenhouse Gas Emissions from Wastewater Treatment System - Devkota, Rohini Prasad (Journal of the Institute of Engineering, 2011)
Besides its great potential in controlling water pollution from different sources, waste water treatment system generates significant amount of greenhouse gases. Hence, reducing the emission of greenhouse gases from the wastewater treatment plants is the major concern. The correct understanding and estimation of the greenhouse gases emitted from different points of the plan is essential to tackle this challenge. This research has attempted to evaluate and quantify the greenhouse gases, mainly methane and nitrous oxide, emissions from the wastewater treatment system under varying conditions of temperature and oxygen. The sludge samples were collected from the septic tank, aeration tank, denitrification tank and digestion tank to examine the emission of greenhouse gases from the samples with and without nutrients and volatile fatty acids(VFA). To examine the effect of temperatures on the emission of greenhouse gases, experiments were designed under different temperatures by keeping reactors at 4º C, 20º C, 25º C, 30º C, 37º C and 50º C. Similarly, experiments were carried out at 37º C under different amount of oxygen supply (0, 0.1, 0.4, 1.0 and 2.0 mg/L) to examine the role of oxygen in greenhouse gases emission. Experimental results showed that the rate of emission of CH4 gas from the sludge sample was enhanced with the presence of glucose, nutrients and VFA. Rate of CH4 production was well correlated with sludge temperature. It was similar for all sludge samples taken from different points of the treatment plant. Rate of production was found highest for digestion sludge and least fir septic sludge. CH4 production was started earlier and found fastest from the digestion sludge. An inverse relationship was found between the rate of CH4 emission and the amounts of oxygen present in the sludge sample. However, N2O emission was not detected at all. Keywords: Methane; Anaerobic; Temperature; Nutrients; Wastewater; Sludge DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5110 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 178-187 Uploaded Date: 20 July, 2011